Unexpected low soil-transmitted helminth prevalence in the Butha-Buthe district in Lesotho, results from a cross-sectional survey. Issue 1 (December 2017) - Moser, Wendelin; Labhardt, Niklaus; Cheleboi, Molisana; Muhairwe, Josephine; Keiser, Jennifer
Abstract Background Soil-transmitted helminth (STH) infections withAscaris lumbricoides, hookworm andTrichuris trichiura affect large parts of the world's population. For the implementation of national STH control programs, e.g. preventive chemotherapy (treatment with albendazole and mebendazole), the spatial distribution and prevalence of STH infections must be known. However, for Lesotho only little data were available and the STH distribution remains largely unknown. Methods In early 2016, a cross-sectional parasitological STH survey was conducted including six different primary schools in the Butha-Buthe district of Lesotho. In each school stool samples were collected from 50 children (age 8–14 years) and analysed with a duplicate Kato-Katz thick smear for the presence ofA. lumbricoides, hookworm andT. trichiura . Results A total of 301 children provided a stool sample. All children were negative forA. lumbricoides andT. trichiura . Only two children from one primary school showed a light hookworm infection. Conclusion Our data indicate a low prevalence of STH infections in the Butha-Buthe district of Lesotho. Additional parasitological surveys on the prevalence and the spatial distributions of STH infections across the entire country of Lesotho are needed.